Widely tunable single bandpass microwave photonic filter based on dual‐fiber stimulated Brillouin scattering. Issue 4 (2nd January 2019) - Yan, Juanjuan; Li, Liwei; Yi, Xiaoke; Chew, Suen X.
Abstract: A new technique to achieve a single bandpass microwave photonic filter (MPF) with wide tunability based on stimulated Brillouin scattering is proposed. The MPF cascades the Brillouin frequency shifter and amplification based on a dual‐fiber structure. The experimental results present a single bandpass MPF located at 21.4 GHz with a 3‐dB bandwidth of 38 MHz and an out‐of‐band rejection ratio over 30 dB. The proposed single bandpass MPF also successfully demonstrates a wide‐band tuning over 40 GHz, which is achieved by employing a frequency shifter based on carrier suppressed single‐sideband modulation scheme in the structure.